Crossing the Barbed Gate Experiences of Accessing the Research Participants for their Informed Consents through the Gatekeepers in an Indian School - Tripathy, Dipankar (JOURNAL OF INDIAN EDUCATION, 2013)
Gaining access to the research sites, participants and their informed consents is not always an easy process. It involves negotiations and compromises with the gatekeepers. Hence, researchers spend considerable amount of time since inability in negotiation and access, results into unsuccessful research. Yet, researchers, particularly engaged in qualitative research, often neglect this process and face dilemmas due to the ethical obligations. When university ethics committees demand voluntary participation of the participants, power relations between the gatekeepers and the participants underpin the co-production of the research data. Therefore, researchers must continually reflect upon the decision-making processes, around the routes of access, that might influence the research data collected. In this paper, how the access, re-access and informed consents of the participants were gained in a school for a qualitative study in India has been reflected, and this includes addressing the ethical underpinnings involved therein. As such, these experiences were gained as a beginning researcher and it is hoped that sharing these will benefit other beginners conducting their qualitative studies, particularly in India.